Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

King King théorie - Despentes, Virginie (Grasset, 2006)
J'écris de chez les moches, pour les moches, les frigides, les mal baisées, les imbaisables, toutes les exclues du grand marché à la bonne meuf, aussi bien que pour les hommes qui n'ont pas envie d'être protecteurs, ceux qui voudraient l'être mais ne savent pas s'y prendre, ceux qui ne sont pas ambitieux, ni compétitifs, ni bien membrés. Parce que l'idéal de la femme blanche séduisante qu'on nous brandit tout le temps sous le nez, je crois bien qu'il n'existe pas. V.D.
Keywords: 2000 à aujourd'hui; 2000-2009; anticapitalisme; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; europe; fem1000; fem7000; france; hétérosexisme; identités LGBTQIA2+; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; violences; violences sexistes et sexuelles; études littéraires

Quand les femmes écrivent la guerre : transformation du genre et du monde dans Les hommes qui marchent de Malika Mokeddem et Iran, les rives du sang de Fariba Hachtroudi - Bélanger, Marie-Ève (Université du Québec à Montréal, 2005)
Keywords: 1900-1999; 1990-1999; IREF; afrique; algérie; asie; discipline; guerre; iran; mémoires/thèses; périodes historiques; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Gender, discourse, and desire in twentieth-century Brazilian women's literature - Pinto, Cristina Ferreira (Purdue studies in Romance literatures, 2004)
This study by Cristina Ferreira-Pinto explores the poetic and narrative strategies twentieth-century Brazilian women writers use to achieve new forms of representation of the female body, sexuality, and desire. Female writers discussed include: Gilka Machado, Lygia Fagundes Telles, Marcia Denser, and Marina Colasanti. While creating new forms, these writers are also deconstructing cultural myths of femininity and female behavior. In order to understand these myths, the book also presents new readings of some male-authored canonical novels by Jose de Alencar, Machado de Assis, Manuel Antonio de Almeida, and Aluisio Azevedo. The specific focus on female sexuality and desire acknowledges the intrinsic link between sexuality and an individual's sense of identity, and its importance for female identity, given the historical repression of women's bodies and the double standard of morality still pervasive in many Western cultures. In the discussion of the strategies Brazilian female poets and fiction writers employ, Ferreira-Pinto addresses some social and cultural issues that relate to a woman's sense of her own body and sexuality: the characterization of women based on racial features and class hierarchy; marriage; motherhood; the silencing of the lesbian subject; and aging. Ferreira-Pinto's analysis is informed by the works of various and diverse critics and theoreticians, among them Helene Cixous, Teresa De Lauretis, Adrienne Rich, Gloria Anzaldua, Georges Bataille, and Wilhelm Reich.
Keywords: amériques; arts; brésil; corps; discipline; histoire et politique; littérature; maternité; ressource en ligne; régions géographiques; sexualité; thématiques; violences; écriture des femmes*; études littéraires